Symbiotic Posthumanist Ecologies in Western Literature, Philosophy and Art Towards Theory and Practice - Karpouzou, Peggy; Zampaki, Nikoleta (Open textbook library., 2023)
Through the burgeoning fields of Posthumanities and Environmental Humanities, this edition examines the changing conception of human subjectivity, agency, and citizenship as shaped by the dynamic interplays between nature, technology, science, and culture. The proposed ‘symbiotic turn’, (the awareness of the multitude of interactions and mutual interdependencies among humans, non-humans and their environment) aspires to explore the complex recompositions of the “human” in the 21st century. By organizing and promoting interdisciplinary dialogue at multiple levels, both in theory and practice, Symbiotic Posthumanist Ecologies is suggested as a new narrative about the biosphere and technosphere, which is embodied literarily, philosophically, and artistically.